2021
DOI: 10.36692/v13n1-5r
|View full text |Cite
|
Sign up to set email alerts
|

Eletroterapia No Tratamento Da Paralisia Facial Periférica: Revisão Sistemática

Abstract: A Paralisia Facial Periférica (PFP) provém de uma lesão no VII par craniano (nervo facial), responsável pela inervação de dezessete pares de músculos da face. A fisioterapia faz uso de diversos recursos, dentre eles a eletroestimulação, pois possui a capacidade de produzir contração muscular semelhante às contrações voluntárias. O objetivo deste estudo é realizar uma revisão sistemática sobre a utilização da eletroterapia no tratamento da PFP, assim como discutir a qualidades dos estudos, os principais benefíc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In this study, it was observed, through the performance of exercises for the stomatognathic functions and mainly aimed at the rehabilitation of facial mime, which had as objectives the gain of tonus and strength of the oral musculature. 36,37 According to the literature and observed in the reported case, photobiomodulation [38][39][40][41][42] and electrostimulation [43][44][45] associated with orofacial motor exercises 38,41,42,44 promoted positive results in control of saliva flow and ensure greater oromiofacial mobility, accelerating strength gain, maintaining fatigue levels and improving muscle performance. There are still limitations in the literature that do not allow a deeper understanding of the issue, as few articles related speech therapy rehabilitation in patients diagnosed with Tapia´s Syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was observed, through the performance of exercises for the stomatognathic functions and mainly aimed at the rehabilitation of facial mime, which had as objectives the gain of tonus and strength of the oral musculature. 36,37 According to the literature and observed in the reported case, photobiomodulation [38][39][40][41][42] and electrostimulation [43][44][45] associated with orofacial motor exercises 38,41,42,44 promoted positive results in control of saliva flow and ensure greater oromiofacial mobility, accelerating strength gain, maintaining fatigue levels and improving muscle performance. There are still limitations in the literature that do not allow a deeper understanding of the issue, as few articles related speech therapy rehabilitation in patients diagnosed with Tapia´s Syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Research, Society and Development, v. 12, n. 12, e143121244064, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i12.44064 Cruz et al, (2021) realizaram uma revisão sistemática sobre a utilização da eletroterapia no tratamento da paralisia facial periférica. Em geral, os estudos analisados pelos autores mostraram que as correntes elétricas são consideradas uma opção terapêutica válida para o tratamento de paralisia facial periférica.…”
Section: Eletroterapiaunclassified
“…Em geral, os autores concluíram que a eletroterapia é eficaz no tratamento da paralisia de Bell. A maioria dos estudos utilizaram o laser de baixa intensidade no tratamento da paralisia de Bell, com exceção do estudo dos autores Cruz et al (2021), que também utilizaram o laser de alta intensidade considerando-o mais indicado ao comparar com o laser de baixa intensidade.…”
Section: Eletroterapiaunclassified